Relationship between Mothers' Knowledge and Exclusive Breastfeeding Behavior in One Private Hospital in West Indonesia - Lia Kartika; Ferlin Ferlin Tanggulungan; Rita Poppy Febriyanti Sinurat; Ari Tamaro Tambunan; Sumiaty Aiba (Alta Dharma Publisher, 2021)
Abstract. Breast milk is the most exceptional nourishment for babies. Breast milk contains micro and macronutrients, antibodies, fat, and more than hundreds of kinds of supplements that are needed for babies' growth and development. The study aimed to examine the relationship between mothers' knowledge with exclusive breastfeeding behavior. We applied the cross-sectional study design in this study. The population is all mothers from the inpatient and outpatient departments. Using the accidental sampling technique, we involved 150 mothers during June - July 2019. The univariate analysis described the respondents' characteristics, mothers' knowledge, and exclusive breastfeeding behavior. Bivariate analysis using the Chi-Square analysis revealed a significant correlation between the mothers' knowledge and exclusive breastfeeding practice (p=0.011). Additionally, the study found that mothers who had low knowledge have the opportunity of 2.556 times to perform exclusive breastfeeding. The health education towards exclusively breastfeeding behavior is essential to established not only from the prenatal period but also in the postnatal period and continues until the second year of childbirth. Further research needs to examine the husband's support and social culture aspects in demographic data to identify factors for having optimal exclusive breastfeeding